The relation between carbon deposition and hydrogen production in glycerol steam reforming - Go, Yoo-Jin; Go, Gwang-Sub; Lee, Hong-Joo; Moon, Dong-Ju; Park, Nam-Cook; Kim, Young-Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The performance of Ni-based Al2O3 catalyst for glycerol reforming has been investigated in fixed-bed reactor of different operational conditions. Of the three catalysts that are investigated (Ni-Fe-Ce/Al2O3, Ni-Fe-La/Al2O3, Ni-Fe-Cr/Al2O3), Ni-Fe-Ce/Al2O3, with the largest surface area, strong metal support interaction (SMSI) and the smallest carbon deposition after reaction, shows the best activity. Further temperature and pressure tests conducted with this catalyst revealed its superior performance at high temperature and atmospheric pressure in terms of increasing H-2 production and glycerol conversion by inhibiting carbon deposition on the catalyst surface. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: METHANE; NICKEL